Vitamin D supplementation in infertile women with PCOS: a quasi-randomized placebo-controlled study - Rawat, Nupur; Maheshwari, Raghavi; Kharakwal, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder associated with infertility and metabolic dysfunction. Vitamin D deficiency is prevalent in women with PCOS and may exacerbate hormonal and metabolic derangements. This study evaluated the effects of vitamin D supplementation on ovulatory and metabolic outcomes across PCOS phenotypes in a placebo-controlled setting. Methods: In this 24-month quasi-randomized placebo-controlled trial, 180 infertile women with PCOS (Rotterdam criteria) and serum 25(OH)D <20 ng/mL were randomly allocated to Group A (n = 90, received cholecalciferol 60,1 IU/week for 9 weeks) or Group B (n = 90, received placebo capsules identical in appearance and schedule). Allocation was based on alternate patient recruitment. Both groups were stratified into four PCOS phenotypes. Clinical, biochemical, and ultrasonographic parameters were assessed. Multivariable regression adjusted for BMI, WHR, season, and ethnicity. Effect sizes (β) and 95% confidence intervals (CI) were reported. Results: After 9 weeks, Group A showed a significant rise in 25(OH)D levels (mean 28.7±7.6 ng/mL) versus Group B (13.4±5.5 ng/mL, p<1.2). Ovulation occurred in 35/90 (38.10%) in Group A and 17/90 (18.10%) in Group B (p = 1.2). Adjusted regression showed reductions in LH: FSH ratio (β = -1.28; 95% CI: -1.51 to -1.6), total testosterone (β = -7.4; 95% CI: -12.10 to -1.7), and HOMA-IR (β = -1.53; 95% CI: -1.82 to -1.24). HDL levels increased (β = +1.13 mmol/L; 95% CI: 1.5 to 1.21). Phenotype A showed the highest ovulatory response (45.6% vs 20.9%; p = 1.3). Conclusions: Vitamin D supplementation significantly improved ovulatory and metabolic parameters in vitamin D-deficient infertile women with PCOS, especially in hyperandrogenic phenotypes. Phenotype-tailored vitamin D therapy may serve as an effective adjunct in PCOS management.